Impact of supplemental phosphorus source onphosphorus utilization in lactating dairy cattle - Barry J. Bradford; Joseph P. Harner; Michael J. Brouk (Kansas Agricultural Experiment Station Research Reports, 2009)
Supplemental phosphorus (P) in various forms and sources (pellet, meal, liquid, and corn dried distillers grains with solubles; DDGS) were compared in 12 multiparous Holstein cows producing 94.8 lb of milk (115 ± 55 days in milk) in a 4 x 4 Latin square with 21-day periods. The pellet and meal diets contained monocalcium phosphate with a wheat middlings carrier, and the liquid diet contained ammonium polyphosphate in a cane molasses base. The DDGS supplied an organic P source. Cows were blocked by parity, days in milk, and milk production and randomly assigned to treatments. Phosphorus intakes were similar among all 4 diets (116, 116, 119 and 118 g/day for pellet, meal, liquid and DDGS diets, respectively). Cows consuming the liquid diet experienced greater (P<0.001) sugar intakes. Milk yield differed (P = 0.05) among diets, with the DDGS diet yielding the most milk (76.3, 78.1, 75.2 and 80.5 lb/day for pellet, meal, liquid, and DDGS diets, respectively). There were no differences in milk fat and milk protein percentages or in daily lactose production. Excretion of P in feces tended (P = 0.07) to differ among treatments (67.4, 66.3, 57.5, and 60.0 g/day for pellet, meal, liquid and DDGS diets, respectively), resulting in a trend (P = 0.10) for greater P retention from diets, resulting in less P excretion. Secretion of P in milk did not differ among treatments. These data show that supplemental P source does not affect dry matter intake or P intake. Phosphorus source resulted in slight differences in P utilization, but it was not related to sorting of the diet. The DDGS diet showed responses similar to those of inorganic P mineral supplements and had favorable production yields, indicating that DDGS is an adequate substitute for mineral sources of P.; Dairy Day, 2009, Kansas State University, Manhattan, KS, 2009; Dairy Research, 2009 is known as Dairy Day, 2009
Keywords: Kansas Agricultural Experiment Station contribution; no. 10-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1021; Dairy Day; 2009; Dairy; Dried distillers grains; Feces; Phosphorus; Milk yield